What matters for regional economic resilience amid COVID-19? Evidence from cities in Northeast China. (January 2022) - Hu, Xiaohui; Li, Liangang; Dong, Ke
Abstract: This paper examines how the economies of old industrial cities in Northeast China respond to the on-going COVID-19 pandemic crisis. The notion of resistance in regional economic resilience is used to explore what impact factors shape the response to the early stage of the crisis. The analysis reveals significant differences in terms of regional economic impact between COVID-19 and the 2008 financial crisis. We find that large cities are more vulnerable and exposed to the pandemic at its early stage, state agency plays a crucial role in shaping the economic resistance in most cities. Going beyond the existing 2008 financial crisis-induced account on regional economic resilience, this paper argues that regional resistance amid COVID-19 is not merely shaped by economic structural factors but also influenced by state agency in terms of economic restriction and restoration measures. The study suggests that the nature of COVID-19 as a particular context of crisis itself needs to be taken seriously when exploring the determinants and outcomes of regional economic resilience. Highlights: This paper in investigates regional economic resilience under COVID-19 by studying the resistance of Northeast China in the first quarter of 2020. This paper finds that secondary industry structure, overall variety, innovation, specialization, openness and state agency are the main factors shaping regional resistance. Local state agency on containing COVID-19 plays a key role in shaping regional resistance and recovery. The study suggests that the crisis nature of COVID-19 itself needs to be taken seriously when exploring the determinants of regional economic resilience.